Magnetic resonance thermometry in the target volume versus intraluminal probe thermometry for hyperthermia treatment monitoring - Carolina Carrapiço-Seabra; Spyridon N. Karkavitsas; Anton Rink; Nahid Montazeri; Henrike Westerveld; Martine Franckena; Margarethus M. Paulides; Gerard C. van Rhoon; Sergio Curto (Physics and Imaging in Radiation Oncology, 2025)
Background and purpose: Hyperthermia, the elevation of target temperature to 39–44 °C, is monitored using temperature probes. However, these provide limited spatial information, sampling only a few discrete locations. Magnetic resonance (MR) thermometry currently offers an option for three-dimensional (3D) temperature monitoring during hyperthermia. This study compares and correlates temperatures measured by intraluminal probes with MR-based temperatures in (1) the anatomical region containing the intraluminal probes and (2) the hyperthermia target volume (HTV), located at a distance from the probes and representing the primary region of clinical interest. Methods: Thirteen locally advanced cervical cancer (LACC) patients treated with radiotherapy and hyperthermia were included. Hyperthermia was monitored using intraluminal probes and MR thermometry. MR-based temperatures were compared to intraluminal probe temperatures. Repeated measures correlation was applied to correlate probe and MR-based temperatures in the HTV across all data and on a patient-specific basis. Results: MR-based temperatures at probe locations showed good agreement with probe measurements (median absolute error ≤ 0.7 °C). In the HTV, MR-based temperatures deviated by a median absolute error of 0.5 °C from probe temperatures. Repeated measures correlations (rrm) between MR and probe-based HTV temperatures ranged from 0.74 to 0.79 across all data and 0.64–0.96 on a patient-specific basis. Conclusions: MR thermometry demonstrated promising performance for retrospective evaluation of temperature distributions in the HTV. While its current reliability for real-time treatment guidance remains limited, our results support further development towards broader clinical implementation in hyperthermia.